Hepatic Infiltration with Malignant T-cells Manifesting as Impending Acute Liver failure in Mycosis Fungoides with Large Cell Transformation - Yumeng Zhang; Jinming Song; David Rutenberg; Lubomir Sokol (Mediterranean Journal of Hematology and Infectious Diseases)
Here we described a patient with a history of mycosis fungoides who developed large cell transformation manifesting with generalized erythroderma, lymphocytosis, lymphadenopathy and impending acute liver failure (ALF). Three-phase computed tomography of the liver showed neither mass nor hepatomegaly. Liver biopsy confirmed infiltration with malignant CD4+ clonal T-cells. Combination chemotherapy with gemcitabine, dexamethasone, and cisplatin (GDP) resulted in the recovery of liver function and resolution of skin involvement. In Foundation Medicine Hematology Gene Panel, 31 genetic alterations with 11 clinically relevant mutations were identified including ARID2 mutation frequently observed in hepatocellular carcinoma but rarely observed in hematologic malignancies.